Politics of Meaning in Categorizing Innovation: How Chefs Advanced Molecular Gastronomy by Resisting the Label. Issue 2 (February 2020) - Slavich, Barbara; Svejenova, Silviya; Opazo, M. Pilar; Patriotta, Gerardo
This study examines innovators' efforts to conceptualize and communicate their novel work through categorization. Specifically, we view category formation as a controversial process of meaning making, which we theorize through the concept of "politics of meaning" and operationalize through a social semiotics approach. By analyzing the labeling controversies underlying a new culinary style publicized as "molecular gastronomy", we find that innovators' efforts at categorization unfold along four consecutive stages: experimenting with a new style, communicating the new style, contesting the dominant label, and legitimating the category meaning. Our study suggests that a new category's dominant label can substantially deviate from the innovators' intended denotations, yet nonetheless bring that category forward by triggering public negotiations around its meaning, which lead to categorical deepening and legitimation. By putting forward a "politics of meaning" view on categorizing innovation, this work advances our understanding of the connection between labeling and category formation in the context of innovation.